Pycnogonida of the Western Pacific Island, III Recent Smithsonian-Philippines Expeditions. - Child, C. Allan (Washington, D.C. Smithsonian Institution Press, 1988)
Smithsonian contributions to zoology; no.468
Keywords: Arthropoda--South Pacific Ocean--Classification.; Pycnogonida--South Pacific--Classification.; Pycnogonida--Philippines--Classfication.